Auctions implemented by the Federal Reserve Bank of New York during the great recession - Olivier Armantier; John Sporn (Federal Reserve Bank of New York, 2013)
During the Great Recession, the Federal Reserve implemented several novel programs to address adverse conditions in financial markets. Three of these temporary programs relied on an auction mechanism: the Term Auction Facility, the Term Securities Lending Facility, and the disposition of the Maiden Lane II portfolio. These auctions differed from one another in several dimensions: their objectives, rules, and the financial asset being traded. The object of this paper is to document, compare, and provide a rationale for the mechanics of the different auctions implemented by the Federal Reserve during the Great Recession.
Keywords: N22; D02; D44; 330; financial crisis; auctions